2021
DOI: 10.1039/d1mh00857a
|View full text |Cite
|
Sign up to set email alerts
|

Design of ‘tolerant and hard’ superhydrophobic coatings to freeze physical deformation

Abstract: While the development of mechanically durable and abrasion tolerant superhydrophobicity on a rigid interface itself remains a highly challenging task, the design of superhydrophobic coating that can restrict both the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Dhar et al reported an unprecedented chemical approach that restricted the tensile and compressive deformation of the soft, deformable underlying stretchable/compressible substrates as shown in Figure 10A−G. 82 The Michael addition reaction between two small molecules, i.e., 3-(2-aminoethylamino)propyltrimethoxysilane (AEAPTMS), octadecyl acrylate (ODAc), and a multifunctional cross-linker (3Acl/5Acl), was exploited to generate three types of reaction mixtures comprising RMT1 (AEAPTMS and ODAc), RMT2A (AEAPTMS, 3Acl, and ODAc), and RMT2B (AEAPTMS, 5Acl and ODAc) as shown in Figure 10B,E. The deposition of the different reaction mixtures individually on the stretchable polyurethane fabric and the compressible melamine sponge generated a superhydrophobic coating with tailored mechanical property.…”
Section: Design Of "Reactive'' Interfaces Formentioning
confidence: 99%
See 3 more Smart Citations
“…Dhar et al reported an unprecedented chemical approach that restricted the tensile and compressive deformation of the soft, deformable underlying stretchable/compressible substrates as shown in Figure 10A−G. 82 The Michael addition reaction between two small molecules, i.e., 3-(2-aminoethylamino)propyltrimethoxysilane (AEAPTMS), octadecyl acrylate (ODAc), and a multifunctional cross-linker (3Acl/5Acl), was exploited to generate three types of reaction mixtures comprising RMT1 (AEAPTMS and ODAc), RMT2A (AEAPTMS, 3Acl, and ODAc), and RMT2B (AEAPTMS, 5Acl and ODAc) as shown in Figure 10B,E. The deposition of the different reaction mixtures individually on the stretchable polyurethane fabric and the compressible melamine sponge generated a superhydrophobic coating with tailored mechanical property.…”
Section: Design Of "Reactive'' Interfaces Formentioning
confidence: 99%
“…Such characteristics are of utmost importance for realistic and diverse applications of the bioinspired coating. In this regard, the environment-friendly Michael addition reaction between amine and acrylate requiring mild operational conditions would provide a prospective platform to tailor the bioinspired water wettability and other relevant physical properties (Figure )including transparency, mechanical property, porosity, etc.following simple and scalable fabrication processes. In the past, the catalyst-free Michael addition reaction was successfully extended to produce amplified “reactive” surfaces. , Ford et al studied the ability of growing different nanostructures on selected substrates following the catalyst-free aza-Michael addition reaction between branched polyethylenimine (BPEI) and dipentaerythritol penta-acrylate (5-Acl) that resulted in hyperbranched poly­(ester amines) cross-linked thin films with surface amplified functional groups . In 2012, Bechler et al capitalized on this concept of a nanostructured, “reactive” polymeric film of BPEI/5Acl to construct a relatively thick (∼750 nm) multilayer coating following the layer-by-layer deposition approach .…”
Section: Design Of “Reactive’’ Interfaces For Superhydrophobicity: Su...mentioning
confidence: 99%
See 2 more Smart Citations
“…Towards this goal, Ge et al developed an in situ oil collection device that was aided by the application of external force [ 28 ]. Such continuous oil collection processes require oil absorbing materials with high mechanical performances as well as excellent hydrophobic and lipophilic properties [ 29 ]. Many strategies have been developed for the modification of commercial melamine foams, polyurethane foams or metal foams (pore sizes ranging from 100 to 500 µm) to create materials with the desired characteristics for the continuous clean-up of large-scale oil spills [ 22 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%